Molecular Dynamics Simulations of Nanoparticle Interactions with a Planar Wall: Does Shape Matter? (Communications in Computational Physics, 2020)
We investigate the hydrodynamic interactions of spherical colloidal nanoparticles and nano tetrahedra near a planar wall by means of molecular dynamics(MD) simulations of rigid particles within an all-atom solvent. For both spherical andnano-tetrahedral particles, we find that the parallel and perpendicular components ofthe local diffusion coefficient and viscosity, show good agreement with hydrodynamictheory of Faxén and Brenner. This provides further evidence that low perturbationsfrom sphericality of a nanoparticle's shape has little influence on its local diffusive behaviour, and that for this particular case, the continuum theory fluid dynamics is valideven down to molecular scales.